1997
DOI: 10.1590/s0301-80591997000200015
|View full text |Cite
|
Sign up to set email alerts
|

Resistência de genótipos de sorgo a Contarinia sorghicola (Coq.) (Diptera: Cecidomyiidae) e Diatraea saccharalis (Fabr.) (Lepidoptera: Pyralidae) e influência sobre parasitóides

Abstract: Avaliou-se a resistência de genótipos de sorgo (Sorghum bicolor) a Contarinia sorghicola (Coq.) e Diatraea saccharalis (Fabr.) e sua influência sobre parasitóides. Foram realizados ensaios em duas épocas de plantio, anotando-se o número de insetos (pragas e parasitóides) e calculando-se a percentagem de parasitismo. O genótipo AF-28 destacou-se como o mais resistente às duas espécies pragas, ocorrendo o inverso com o TX-2567; as maiores percentagens de parasitismo de C. sorghicola por Tetrastichus sp. (Hymenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This study showed a mean stem borer injury of 12.11% for hybrid BRS373 without insecticide treatment, which is equivalent to twice that found by Lara et al. (1997) when evaluating the pest infestation in sorghum. These authors also found greater stem borer injury of SCB in the 2nd‐season planting, which was about three times lower than that found herein in the plants without chlorantraniliprole treatment.…”
Section: Discussionsupporting
confidence: 70%
“…This study showed a mean stem borer injury of 12.11% for hybrid BRS373 without insecticide treatment, which is equivalent to twice that found by Lara et al. (1997) when evaluating the pest infestation in sorghum. These authors also found greater stem borer injury of SCB in the 2nd‐season planting, which was about three times lower than that found herein in the plants without chlorantraniliprole treatment.…”
Section: Discussionsupporting
confidence: 70%
“…As the number of cuts and plant ages explained the spatial variation of D. saccharalis and the tachinid populations, the tachinids could respond either to the spatial variation of their host or, to a lesser extent, to habitat modifications, because tachinids also responded significantly to different varieties in the São João Mill, a response not observed in D. saccharalis (table 5). Host plants of arthropod pests may directly or indirectly affect parasitoids and predators through multitrophic interactions ( Lara et al., 1997; Bottrell et al., 1998; Gullan and Cranston , 2000). Thus, underlying characteristics of sugarcane cultivation may directly and indirectly affect the spatial distribution of the tachinids, through the induction of different parasitoid dispersal patterns and changes in host distribution, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Varieties can be either susceptible or resistant to a given pest ( Gullan and Cranston , 2000), and therefore diversified systems seem to be a major determinant in promoting higher spatial and temporal variability of pest populations than homogeneous crop systems. Host plants of arthropod pests may also affect parasitoids and predators directly or indirectly through multitrophic interactions ( Lara et al., 1997; Bottrell et al., 1998; Gullan and Cranston , 2000). Multitrophic effects often involve interactions that are not well understood, and their impact on natural enemies and biological control are difficult to predict ( Bottrell et al., 1998).…”
Section: Introductionmentioning
confidence: 99%